(untitled) (Global Journal of Human-Social Science, 2023)
Self-isolation and social distancing is recommended by WHO to prevent the spread of COVID-19 By the mid of March many procedures were done to achieve social distancing such as schools shops and malls closure Most Schools shift their mode of teaching from face to face to distance learning The purpose of this paper is to understand the effect of the sudden shift from face to face learning to distance learning to Design Students from University of Technology and Applied Sciences Nizwa It mainly shed light on challenges and opportunities that students faced during their distance studies and how they practiced the SRL To reach a good understanding of this a quantitative questionnaire from three parts was distributed electronically during distance learning The questionnaire covers facilities and physical study atmosphere psychological effect and study performance SRL theory is used to measure students learning control The results showed that students had faced many challenges during their studies such as personal devices software availability a quiet place a positive atmosphere and family responsibilities Moreover the negative psychological effect on Design students affects their courses outcome as well as their grades Overall the level of satisfaction of online learning was low and most students were waiting for the moment to go back to campus